Serious infections in patients with ankylosing spondylitis with and without TNF blockers: a systematic review and meta-analysis of randomised placebo-controlled trials. Issue 10 (28th July 2009) - Fouque-Aubert, Anne; Jette-Paulin, Laetitia; Combescure, Christophe; Basch, André; Tebib, Jacques; Gossec, Laure
Abstract : Background: Tumour necrosis factor (TNF) blockers are known to increase the risk of serious infections in rheumatoid arthritis. Despite wide use of TNF blockers in ankylosing spondylitis (AS), the infection risk has never been evaluated in this disease. Objectives: To assess serious infections in patients with AS not exposed and exposed to TNF blockers. Methods: A systematic literature review up to May 2008 using PubMed, EMBASE and Cochrane Library was performed. All randomised controlled trials (RCTs) published between 1995 and 2008 monitoring serious infections, treated with non-steroidal anti-inflammatory drugs (NSAIDs) or TNF blockers, were included. Infection risks were calculated by naive pooling and for 100 patient-years (pyrs) of exposure. To assess the serious infection risk with TNF blockers, a meta-analysis of RCTs was performed using Mantel–Haenszel's method with several sensitivity analyses. Results: Fourteen RCTs were included (3345 patients). With placebo or NSAIDs (N=2202), two serious infections were observed (0.09%, range 0.01% to 0.3%)—that is, 0.4/100 pyrs. In TNF blocker trials, two serious infections were observed with placebo (2/500, 0.4% (0.0% to 1.4%), ie, 1.0/100 pyrs) versus 14 serious infections with TNF blockers (14/996, 0.7% (0.3% to 1.4%), ie, 1.9/100 pyrs). Meta-analysis of the RCTs showed that the increase in serious infections with TNF blockers compared with placebo was not significant: risk difference=0.4% (−8% to 1.6%). Conclusions: The absolute risk of serious infections in patients with AS not exposed to TNF blockers is low. The absolute risk of serious infections in patients receiving TNF blockers is higher, but the difference was found to be not significant, possibly through lack of power. Continued monitoring is necessary.